Alkoxyallene‐ynes: Selective Preparation of Bicyclo[5.3.0] Ring Systems Including a δ‐Alkoxy Cyclopentadienone. Issue 14 (19th February 2016) - Tap, Aurélien; Lecourt, Camille; Dhambri, Sabrina; Arnould, Mathieu; Galvani, Gilles; Nguyen Van Buu, Olivier; Jouanneau, Morgan; Férézou, Jean‐Pierre; Ardisson, Janick; Lannou, Marie‐Isabelle; Sorin, Geoffroy
Abstract: The development of an intramolecular rhodium(I)‐catalyzed Pauson–Khand reaction of alkoxyallene‐ynes with a proximal alkoxy group is reported. This reaction, in the presence of a [Rh(cycloocta‐1, 5‐diene)Cl]2 /propane‐1, 3‐diylbis(diphenylphosphane) system under a CO atmosphere, constitutes a powerful tool for selectively accessing carbo‐ and heterobicyclo[5.3.0] frameworks featuring an enol ether moiety. Through this procedure, a straightforward access to guaiane skeletons with a tertiary hydroxy group at the C10 position was achieved. Abstract : Guaiane skeleton synthesis : Intramolecular rhodium‐catalyzed Pauson–Khand cyclocarbonylation reactions of alkoxyallene‐ynes with the alkoxy group at the proximal position were successfully performed to access [5, 7] ring systems bearing an enol ether. This procedure offers a straightforward access to guaiane skeletons with a tertiary hydroxy group at the C10 position (see scheme; Ts=toluene‐4‐sulfonyl).